Analysis of Microseismicity Framing ML > 2.5 Earthquakes at The Geysers Geothermal Field, California. Issue 8 (22nd August 2019) - Bentz, Stephan; Martínez‐Garzón, Patricia; Kwiatek, Grzegorz; Dresen, Georg; Bohnhoff, Marco
Abstract: Preparatory mechanisms accompanying or leading to nucleation of larger earthquakes have been observed at both laboratory and field scales, but conditions favoring the occurrence of observable preparatory processes are still largely unknown. In particular, it remains a matter of debate why some earthquakes occur spontaneously without noticeable precursors as opposed to events that are preceded by an extended failure process. In this study, we have generated new high‐resolution seismicity catalogs framing the occurrence of 20 M L > 2.5 earthquakes at The Geysers geothermal field in California. To this end, a seismicity catalog of the 11 days framing each large event was created. We selected 20 sequences sampling different hypocentral depths and hydraulic conditions within the field. Seismic activity and magnitude frequency distributions displayed by the different earthquake sequences are correlated with their location within the reservoir. Sequences located in the northwestern part of the reservoir show overall increased seismic activity and low b values, while the southeastern part is dominated by decreased seismic activity and higher b values. Periods of high injection coincide with high b values and vice versa. These observations potentially reflect varying differential and mean stresses and damage of the reservoir rocks across the field. About 50% of analyzed sequences exhibit no change in seismicity rate in response to the large main event. However, we find complex waveforms at the onset of the main earthquake, suggesting that small ruptures spontaneously grow into or trigger larger events. Key Points: We statistically analyze temporal properties of seismicity utilizing enhanced seismicity catalogs framing 20 M L > 2.5 earthquakes at The Geysers Triggered aftershocks are mostly restricted to the northwestern part of the geothermal field Larger events may be preceded by isolated smaller earthquakes at approximately the same location